Long-Term Reliability of Neuroendoscopic Aqueductoplasty in Idiopathic Aqueductal Stenosis-Related Hydrocephalus. Issue 1 (7th June 2018) - Marx, Sascha; Baldauf, Joerg; Matthes, Marc; Gaab, Michael R; Schroeder, Henry W S
Abstract: BACKGROUND: During the 1990s, endoscopic aqueductoplasty (AP) was considered to be a valuable alternative to endoscopic third ventriculostomy (ETV) in treating hydrocephalus related to idiopathic aqueductal stenosis (iAS), with promising short-term outcomes. OBJECTIVE: To evaluate the long-term outcome of AP in the treatment of iAS. METHODS: Long-term follow-up clinical examinations and magnetic resonance (MR) imaging were performed for patients treated by an AP for iAS in our department. RESULTS: Twenty patients (14 female, 6 male, mean age 41.7 yr, range 0.5-67 yr) were treated between 1996 and 2002. Two patients were lost to long-term follow-up. One patient died 6 mo after AP, but death was not related to the procedure. The mean follow-up for the remaining 17 patients was 120 mo. Clinically relevant aqueductal reclosure was observed in 11/17 patients after a mean follow-up of 53.4 mo. These 11 patients underwent ETV, which has been successful during further follow-up. Four of the six remaining patients presented with no clinical symptoms, although aqueductal restenosis was observed on MR imaging. Thus, the overall failure rate of AP was 88.2%. The failures were homogeneously distributed over the entire follow-up period. CONCLUSION: AP has a high risk of failure during long-term follow-up and is not recommended as the first choice of treatment in hydrocephalus caused by iAS. ETV should be done instead. AP may be reserved for a limited number of patients in whom ETV is not feasible but should be combined with stenting to avoid reclosure of the aqueduct.